Semantic based mapping from XML to relations - Kamsuriah, Ahmad; Reduan, Samad (2012)
Extensible Markup Language (XML) is s t i l l the dominant standard for data interchange and data representation on the web. With large amount of data now being represented in XML in the web, the question raised is how to store, index, access and retrieve the information effectively. Even though XML can ex i s t as a database on i t s own but the c apabi l i ty i s v e ry limited when compared with sophisticated storage and query ability provided by existing relational database. Now, relational databases are the most widely used technology for storing XML data, where they store the data efficiently and with no redundancy because each unit of information is saved in only one place through normalization step. The process of transferring XML to relations is called mapping and these processes occur frequently. There are many approaches available for mapping XML to relations but the focus are mostly on the structure. The semantic constraints for XML as expressed in functional dependencies are being ignored. In this study we proposed an algorithm for the mapping that is based on the normalization steps through the functional dependencies. When compared with the existing mapping approaches, we proved that our proposed approach is more efficient in terms of generating relations that satisfies the Third Normal Form (3NF.)